High-resistivity nitrogen-polar GaN for GaN/AlGaN high electron mobility transistors by metalorganic chemical vapor deposition - Yang Wang (AIP Publishing LLC, 2021)
Nitrogen-polar (N-polar) III-nitride has natural advantages in the fabrication of electronic devices. In this work, unintentionally doped N-polar GaN films were grown on sapphire substrates by metalorganic chemical vapor deposition. By optimizing the growth parameters including growth temperature, pressure, and V/III ratio, N-polar GaN with a relatively high sheet resistivity of 3.6 × 105 Ω/sq was achieved. The secondary ion mass spectroscopy and x-ray diffraction measurement results demonstrate that the increased carbon impurity concentration is primarily responsible for the high resistivity. Moreover, N-polar GaN/Al0.25Ga0.75N heterojunctions were deposited on the high-resistivity N-polar GaN template. An extremely high-density two-dimensional electron gas of up to 1.12 × 1013 cm−2 was realized at the interface between the Al0.25Ga0.75N and the GaN. It is reasonably believed that the experimental results obtained here are beneficial for the development of high-performance N-polar GaN-based electronic devices.